PERLINDUNGAN KONSUMEN SEKTOR JASA KEUANGAN DITINJAU DARI UNDANG-UNDANG NOMOR 21 TAHUN 2011 DAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 - Zepryanto Saragih; Bismar Nasution; Windha Windha (Universitas Sumatera Utara, 2016)
CONSUMER PROTECTION BASED ON FINANCIAL SERVICES SECTOR LAW NUMBER 21 OF 2011 AND LEGISLATION OF 1999 NUMBER 8 *) Zepryanto P. Saragih **) Bismar Nasution ***) Windha ABSTRACT Consumer law in perspective Law Number 8 of 1999 on Consumer Protection is the ultimate consumer. According to Law Number 21 of 2011 on the Financial Services Authority, the consumer is not only the end consumer, but also among consumers. Limitation of consumers in these two laws have an impact on consumer protection. The issues raised in this paper is how to limit consumers in the financial services sector, how the form of legal protection for the consumer in terms of Law Number 21 of 2011 on the Financial Services Authority and Law Number 8 of 1999 on Consumer Protection, and how the position of Law Number 8 of 1999 on Consumer Protection against Law Number 21 of 2011 on the Financial Services Authority related to consumer protection. Methods of research conducted in this thesis is the workmanship that relies on normative legal norms, this study is descriptive and analytical, because it describes the problem in a way translate. The method of data collection is library research, which conducts research using data from a variety of reading materials, such as legislation, books, newspapers, and Internet sites are considered relevant to the subject matter covered. Consumer financial services sector, particularly investors in the capital market to the attention of the consumer protection financial services sector. Birth of Law Number 21 of 2011 on the Financial Services Authority puts consumers not only as users, end users or beneficiaries, but also those who commercialize goods and / or services. These developments affect the legal protection of the consumer in a preventive and repressive. The use of the principle of lex specialis derogate lex generalis and principle of lex posterior derogate lex priori is needed in order to provide clarity to the provisions of this law to see the position of Law Number 8 of 1999 on Consumer Protection of the Law Number 21 of 2011 on the Financial Services Authority related to consumer protection. *) Mahasiswa Hukum Ekonomi Fakultas Hukum Universitas Sumatera Utara **) Pembimbing I, Dosen Fakultas Hukum Universitas Sumatera Utara ***) Pembimbing II, Dosen Fakultas Hukum Universitas Sumatera Utara